In vitro inhibition of ammonia toxicity in seawater fish pond systems by probiotic-glucose combination. - Javier, Cherisse Elisea Alojado
The study reports on the efficiency of glucose - Purepond 1 treatments in lowering the level of ammonia in amrine pond systems. Seawater ample obtained from hatchery sources, were treated with different ratios of glucose - Purepond 1. The absorbance values and physico - chemical parameters were monitored. The most effective quantity ratio of glucose - Purepond 1 in lowering the level of ammonia was 3.0 g glucose + 5.0 g Purepond 1. The most deficient in lowering the level of ammonia are the quantity ratios which consists of 5.0 g glucose + 7.0 Purepond 1; and, 5.0 g glucose+ 3.0 g Purepond 1. There was a decrease in the pH, dissolved oxygen and temperature values during the duration of the study.